2020
DOI: 10.1017/s0007114520002755
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Bacillus subtilis DSM 29784 and enzymes, alone or in combination, as alternatives for antibiotics to improve growth performance, digestive enzyme activity, anti-oxidative status, immune response and the intestinal barrier of broiler chickens

Abstract: This study investigated the effect of Bacillus subtilis DSM 29784 (Ba) and enzymes (xylanase and β-glucanases; Enz), alone or in combination (BE) as antibiotic replacements, on the growth performance, digestive enzyme activity, immune response, and intestinal barrier of broiler chickens. In total, 1200 1-d-old broilers were randomly assigned to five dietary treatments, each with six replicate pens of 40 birds for 63 d as follows: A) basal diet (control), supplemented with B) 1×109 colony-forming units (cfu)/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 87 publications
13
36
1
Order By: Relevance
“…In the current study, B. amyloliquefaciens LFB112 substantially upregulated IgA and IgG concentrations in the serum of broilers on days 21 and 39, indicating an improvement in immune function. The results of this study are consistent with the research in which supplementation of Bacillus subtilis DSM 29,784 significantly upregulated serum IgA and IgG contents compared to the control or 250 mg/kg enramycin group [ 68 ]. Another report demonstrated that broilers receiving Saccharomyces boulardii and Bacillus subtilis B10 (1 × 10 8 CFU/kg of feed) significantly increased the number of IgA-positive cells in the jejunum, as well as the cytokine IL-6, TNF-α, TGF-β, and sIgA concentration levels in both jejunum and ileum [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, B. amyloliquefaciens LFB112 substantially upregulated IgA and IgG concentrations in the serum of broilers on days 21 and 39, indicating an improvement in immune function. The results of this study are consistent with the research in which supplementation of Bacillus subtilis DSM 29,784 significantly upregulated serum IgA and IgG contents compared to the control or 250 mg/kg enramycin group [ 68 ]. Another report demonstrated that broilers receiving Saccharomyces boulardii and Bacillus subtilis B10 (1 × 10 8 CFU/kg of feed) significantly increased the number of IgA-positive cells in the jejunum, as well as the cytokine IL-6, TNF-α, TGF-β, and sIgA concentration levels in both jejunum and ileum [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, up-regulated expression of IL-2 and IL-10 in the ileum was observed in an unchallenged experiment ( Park et al., 2020 ). The reason may be that B. subtilis or B. licheniformis could inhibit avian pathogenic growth and enhance functioning of the gut barrier ( Wang et al., 2017 ; Medina et al., 2019 ; Wang et al., 2020 ). Interestingly, based on our results, B. licheniformis was more effective than B. subtilis in increasing serum immunoglobulins and decreasing the pro-inflammatory cytokine, IL-6, further research is required to elucidate the exact, mechanism hereof.…”
Section: Discussionmentioning
confidence: 99%
“…in this study significantly improved nutrient intake of protein, lipid, fiber, and organic matter. This can be due to increasing bacterial enzyme activity and increasing digestive enzyme activity, so there is improving nutrient intake, improving digestion, and nutrient absorption, which finally could improve the gut health status and production performance of chickens [25], [26], [27], [28], [29]. The microorganisms in feed supplements are generally regarded as safe (GRAS) and are important components of natural gastrointestinal tract microbiota.…”
Section: Resultsmentioning
confidence: 99%